Worldmaking in the long Great War : how local and colonial struggles shaped the modern Middle East - Wyrtzen, Jonathan, 1973- (Columbia University Press, 2022)
"How did the postwar political order in the Middle East and North Africa come to be defined? While it is commonly argued that this order came about due to British and French forces imposing a series of artificial boundaries they negotiated in wartime and postwar agreements, Wyrtzen adds that it was also a result of complex and violent struggles among various colonial and local forces reimagining what the political space in the post-Ottoman, post-WWI MENA region should look like. Reimagining the Middle East provides a history of revolts that occurred in the 1920s across North Africa and the Middle East in the aftermath of the postwar "peace settlement" brokered in Paris. Wyrtzen's scope includes major political and military mobilizations to create or defend a local defined political order using examples from the Rif Republic in Morocco, the Sanusi State in the northern part of Libya, the Syrian Revolt, the Kurdish Revolts in the Zagros Mountains, to the state forming movements in the Arabian Peninsula. The reality was that the boundaries and distribution of control the treaties outlined by the British and the French bore little resemblance to realities on the ground. This gap only grew over subsequent years as various groups forced dramatic renegotiations. Some units that emerged like the Turkish Republic and the Kingdom of the Saudi Arabia were successful in the long-term. Others like the Kingdom of the Hejaz, the Rif Republic, the Kingdom of Kurdistan, the Ararat Republic, or the Sanusi state were not. But, these political entities that eventually failed also profoundly influenced how the postwar map was defined. This book provides a fresh alternative look at the creation of the twentieth-century world order and is a notable contribution to the fields of Middle East history and international affairs"-- Provided by publisher.
Keywords: World War, 1914-1918 -- Middle East.; Geopolitics -- Middle East.; Middle East -- Politics and government -- 1914-1945.; Middle East -- Foreign relations -- 20th century.; Moyen-Orient -- Politique et gouvernement -- 1914-1945.; Moyen-Orient -- Relations extérieures -- 20e siècle.; HISTORY -- Military -- World War I.; Diplomatic relations; Geopolitics; Politics and government; Middle East; 1900-1999